The Strategies of Ajengans in Mediating Islam and Local Traditions in Rural West Bandung Regency - Mohammad Taufiq Rahman; Paelani Setia; Asep Iwan Setiawan (UIN Sunan Gunung Djati Bandung, 2023)
Islam is not present in a society empty of culture but is here to find local traditions that develop and run amid a pluralistic society so that local traditions are maintained and packaged with Islamic values. Among the local traditions still growing in the community is